If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(-9m + 1) = 8(6m + -1) Reorder the terms: 10(1 + -9m) = 8(6m + -1) (1 * 10 + -9m * 10) = 8(6m + -1) (10 + -90m) = 8(6m + -1) Reorder the terms: 10 + -90m = 8(-1 + 6m) 10 + -90m = (-1 * 8 + 6m * 8) 10 + -90m = (-8 + 48m) Solving 10 + -90m = -8 + 48m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-48m' to each side of the equation. 10 + -90m + -48m = -8 + 48m + -48m Combine like terms: -90m + -48m = -138m 10 + -138m = -8 + 48m + -48m Combine like terms: 48m + -48m = 0 10 + -138m = -8 + 0 10 + -138m = -8 Add '-10' to each side of the equation. 10 + -10 + -138m = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -138m = -8 + -10 -138m = -8 + -10 Combine like terms: -8 + -10 = -18 -138m = -18 Divide each side by '-138'. m = 0.1304347826 Simplifying m = 0.1304347826
| (n-3)*8=56 | | (12+12u)+3= | | (n-9)*4=36 | | 4x+3=9+3 | | 5x+220=13x-12 | | ln(5x^2)/ln(6x^3) | | 8x=24+4x | | 3x-11=-73-9x | | 5(11-2x)=15 | | 4(-3)+2y=8 | | 9y-30+4y=9 | | n*7=108 | | n+22=40 | | 3(4x+5)=27 | | 4(-3)+2y=8findy | | n^2-n-12/4-n^2(x)n-2/n-4 | | n-2/n-4 | | n^2-n-12/4-n^2 | | 40+90+10x=180 | | 70+80+5x=180 | | (v^2+gn)(v^2-gn)= | | 9=-3/9 | | 2g^2-14g-220=0 | | n+24=37 | | x^2-20x-40=0 | | 5(x-2)=3(x-1)+1 | | 102+32+x+25=180 | | (-12.2)(-5.6)= | | -2x-3x+x+10=2x | | 4x-x+2=2x-x+15 | | 50+35+x-2=180 | | 2m^2-m/2 |